The public perceptions of urban sanitation infrastructure: a cross-sectional study in Kegalle township in Sri Lanka - B.K.A. Bellanthudawa; Samitha Udayanga; Poornima Rajapaksha; Nawala Mudiyanselaya Semini Kushara Nawalage; Rajitha Senanayake; Senani Meegalla; Jayasuriya Mudiyanselage Saumya Niroshani Jayasuriya; K.D.K.S. Kumara (Journal of Water, Sanitation and Hygiene for Development, 2023)
Improving public restroom facilities in urban areas can contribute to ensuring the overall living standards of the urban populace. Access to improved sanitation and hygiene is also considered a fundamental human right. Therefore, the present study aims to understand public perceptions of urban public restroom use based on a case study conducted in the municipality of Kegalle township in Sri Lanka. This included a questionnaire survey (N = 115) and in-depth interviews (N = 5). The analysis indicates the urgent need for adequate, accessible, and good-quality sanitary services, particularly in densely populated urban areas of the country. More than 70% of people (from N = 115) indicate that public restrooms are not of good quality due to certain reasons such as poor maintenance and uncleanliness. Despite the insalubrity of public restrooms, many respondents have used them, indicating an urgent policy intervention in operating, and properly maintaining public restrooms in densely populated urban areas of the country. A significant number of respondents indicated that the quality of public restrooms is extremely poor (39%) or poor (31.1%). Around 86.9% of respondents are not satisfied with existing public restrooms, thus, 71.4% believe in reconstructing new public restrooms that pave the way for ensuring access, affordability, quality, and safety. HIGHLIGHTS In total, 70% of respondents indicated that the quality of public restrooms is poor due to poor maintenance.; In total, 86.9% of respondents were dissatisfied with the current state of public restrooms.; In total, 71.4% were in favor of constructing new public restrooms that ensure accessibility, affordability, quality, and safety.; The study demonstrated the demand and need for high-quality sanitation services in densely populated urban areas.;